Synthesis and Optical Performances of a Waterborne Polyurethane-Based Polymeric Dye - Xianhai Hu; Xingyuan Zhang; Jin Liu (International Journal of Polymer Science)
A waterborne polyurethane-based polymeric dye (WPU-CFBB) was synthesized by anchoring 1, 4-bis(methylamino)anthraquinone (CFBB) to waterborne polyurethane chains. The number molecular weight, glass transition temperature, and average emulsion particle size for the polymeric dye were determined, respectively. This polymeric dye exhibited intriguing optical behaviors. The polymeric dye engendered two new absorption bands centered at about 520 nm and 760 nm if compared with CFBB in UV-vis spectra. The 760 nm peak showed hypsochromic shift with the decrease of average particle sizes. The polymeric dye dramatically demonstrated both hypsochromic and bathochromic effects with increasing temperature. The fluorescence intensity of the polymeric dye was much higher than that of CFBB. It was found that the fluorescence intensities would be enhanced from 20°C to 40°C and then decline from 40°C to 90°C. The fluorescence of the polymeric dye emulsion was very stable and was not sensitive to quenchers.